2022
DOI: 10.3174/ajnr.a7605
|View full text |Cite
|
Sign up to set email alerts
|

3D Enhancement Color Maps in the Characterization of Intracranial Atherosclerotic Plaques

Abstract: BACKGROUND AND PURPOSE: High-resolution MR imaging allows the identification of culprit symptomatic plaques after the administration of gadolinium. Current high-resolution MR imaging methods are limited by 2D multiplanar views and manual sampling of ROIs. We analyzed a new 3D method to objectively quantify gadolinium plaque enhancement. MATERIALS AND METHODS:Patients with stroke due to intracranial atherosclerotic disease underwent 7T high-resolution MR imaging. 3D segmentations of the plaque and its parent ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In addition, Sanchez et al. (2022) created a multivariate model, concluding plaque gadolinium (Gd) uptake and plaque burden, and showed that plaque enhancement analysis was more accurate for identifying symptomatic plaques. In this study, both plaque enhancement and plaque burden were found to be significantly associated with symptomatic ICAS, and this result was similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sanchez et al. (2022) created a multivariate model, concluding plaque gadolinium (Gd) uptake and plaque burden, and showed that plaque enhancement analysis was more accurate for identifying symptomatic plaques. In this study, both plaque enhancement and plaque burden were found to be significantly associated with symptomatic ICAS, and this result was similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sanchez et al analyzed 36 patients imaged with 7T HR-MRI and reported that a higher PB was associated with the presence of symptomatic plaque in patients with multiple plaques (OR 6.1). 44 The mean PB for symptomatic plaques was 85±13 and for non-symptomatic plaques was 65±14. 44 Monitoring changes in PB over time may provide valuable information regarding disease progression or response to medical therapy.…”
Section: Neuroimagingmentioning
confidence: 92%
“…Studies have confirmed that the degree of stenosis alone may not fully capture the complexity and hemodynamic significance of intracranial atherosclerotic changes. [42][43][44] Notably, certain features of atherosclerotic plaques are better observed through HR-MRI. PB, enhancement after contrast-Gd administration, and the presence of IPH have emerged as potential biomarkers of plaque instability (figure 2).…”
Section: Plaque Morphology Beyond Degree Of Stenosismentioning
confidence: 99%
See 2 more Smart Citations